Building the Ghanaian nation-state Kwame Nkrumah's symbolic nationalism - Harcourt Fuller (New York, NY Palgrave Macmillan, 2014)
Timeline of important dates in the life of Kwame Nkrumah -- List of Ghanaian premiers -- Map of the Ghana -- The symbolism of Ghanaian nationalism -- Banal symbols of the new nation-state -- Philatelic nationalism -- Economic nationalism -- Civitatis Ghaniensis Conditor -- Exhibiting the nation -- Monumental nationalism -- Pan-African nationalism -- The downfall of Kwame Nkrumah -- The death & resurrection of Kwame Nkrumah -- From redeemer to redeemed.
Includes bibliographical references and index.
Keywords: Nkrumah, Kwame, 1909-1972--Influence.